2‐D low‐profile beam‐switching multibeam antenna based on dimension gradient metasurface. Issue 12 (30th September 2022) - Dou, Haipeng; Han, Liping; Li, Li; Su, Jinrong; Chen, Xinwei; Zhang, Wenmei; ,
Abstract: A 2‐D multibeam antenna based on the dimension gradient metasurface is proposed in this paper. The metasurface is composed of four subunits formed by square patches with the dimension gradient in a 5 × 5 pattern. When the dimension gradient of subunits is adjusted, the beam direction in the azimuth plane can be switched in a larger range. Furthermore, by introducing L‐shaped slots in the ground plane and two stubs on the feeding lines, the peak gain, sidelobe level and isolation of the antenna can be improved. Meanwhile, the antenna maintains a low profile of 0.06  λ 0 . The measured results show that the impedance bandwidth of the antenna is 16.5% (5.5–6.49 GHz). Four beams are generated and pointed at ( φ 0, θ 0 ) = (70°, 23°), (160°, 24°), (250°, 21°), and (340°, 24°). The peak gains of the beams reach 8.54 dBi.